Genetic analysis of the ATG16L1 c.898A>G (p.T300A) variant in acute and chronic pancreatitis - Neubauer, Claudia; Ewers, Maren; Schulz, Hans-Ulrich; Weiß, Frank Ulrich; Lämmerhirt, Felix; Lerch, Markus M.; Bugert, Peter; Landt, Olfert; Algül, Hana; Rosendahl, Jonas; Witt, Heiko (Pancreas, 2022)
Objectives - Human and animal studies suggest an important role of autophagy in the pathogenesis of pancreatitis. ATG16L1 (autophagy-related 16 like 1) is part of a protein complex that is involved in the formation of autophagosomes. The c.898A > G (p.T300A) variant of ATG16L1 is associated with Crohn disease. In this study, we analyzed ATG16L1 c.898A > G (p.T300A) for an association with pancreatitis. - Methods - We genotyped 777 patients and 551 control subjects of German origin by melting curve analysis using fluorescence resonance energy transfer probes. The patient group included 429 patients with nonalcoholic chronic pancreatitis (CP), 141 patients with alcoholic CP, and 207 patients with acute pancreatitis (AP). We classified AP by severity according to the Atlanta symposium 1992. - Results - Allele and genotype frequencies of ATG16L1 c.898A > G (p.T300A) did not differ significantly between patients and controls (G allele frequencies: nonalcoholic CP, 49.9%; alcoholic CP, 48.2%; AP, 49.5%; controls, 52.7%). We found no significant association with the severity of AP either. - Conclusions - Our data do not support a role of ATG16L1 c.898A > G (p.T300A) in the pathogenesis of AP or CP or an influence on the severity of AP.